Surfaces for sports areas. Synthetic turf and needle-punched surfaces primarily designed for outdoor use. Specification for shockpads used with synthetic turf, needle-punch and textile sports surfaces Part 4, (17th January 2023) - British Standards Institution,
No abstract available